Proteomic Analysis of the Cold Stress Response of Ammopiptanthus mongolicus Reveals the Role of AmCHIA in Its Cold Tolerance - Xuting Li; Qi Liu; Rongqi Wu; Jie Bing; Lamei Zheng; Batu Sumbur; Yijun Zhou; Fei Gao (Horticulturae, 2023)
Ammopiptanthus mongolicus, a traditional ethnic medicinal herb, is a rare broad-leaved evergreen shrub in the arid region of central Asia that can survive under extremely low temperatures during winter. In this study, we investigated the cold stress response of A. mongolicus leaves using physiological and proteomic approaches. Cold stress treatment increased the relative electrolyte leakage, proline, and soluble sugar levels and decreased the chlorophyll content in A. mongolicus leaves. Moreover, 93 differentially abundant proteins (DAPs) were identified using two-dimensional electrophoresis, of which 79 were further confirmed via tandem mass spectrometric analysis. The predicted functions of DAPs were mainly associated with photosynthesis in chloroplasts, reactive oxygen species scavenging, defense, and protein synthesis, folding, and degradation. A. mongolicus chitinase A (AmCHIA) is a cold-induced apoplast protein whose transcription is upregulated under cold, osmotic, high-salinity, and mechanical stresses. Recombinant AmCHIA expressed in Escherichia coli exhibits chitinase activity. Here, AmCHIA expression enhanced the cold tolerance of E. coli cells, suggesting that it may contribute to the cold adaptation of A. mongolicus after cold treatment. The present study not only provides important data for understanding the cold stress responses in plants but also serves as a basis for further exploration of the biological functions of cold-induced proteins in A. mongolicus using genetic approaches.